1996
DOI: 10.1161/01.res.78.4.564
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Hydrogen Peroxide and Hydroxyl Free Radical–Induced Intracellular Acidification in Cultured Rat Cardiac Myoblasts

Abstract: After a transient ischemic attack of the cardiac vascular system, reactive oxygen-derived free radicals, including the superoxide (O2-.) and hydroxyl (.OH) radicals can be easily produced during reperfusion. These free radicals have been suggested to be responsible for reperfusion-induced cardiac stunning and reperfusion-induced arrhythmia. Hydrogen peroxide (H2O2) is often used as an experimental source of oxygen-derived free radicals. Using freshly dissociated single rat cardiac myocytes and the rat cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 56 publications
2
36
1
Order By: Relevance
“…In summary, we have shown that in glial cells, HµOµ induces a marked intracellular acidosis, probably via inhibition of glycolysis by ·OH. Since this acidosis is similar to that seen in cardiac myoblasts (Wu, Tsai, Wang, Wu, Wang & Lee, 1996) it is possible that this phenomenon exists in many other cells. This intracellular acidosis may influence the ability of glial cells to regulate the pHï of the microenviroment and may probably contribute, in part, to the neuronal activity and cytotoxic cell oedema seen during brain ischaemic reperfusion.…”
Section: Lactate Productionsupporting
confidence: 55%
“…In summary, we have shown that in glial cells, HµOµ induces a marked intracellular acidosis, probably via inhibition of glycolysis by ·OH. Since this acidosis is similar to that seen in cardiac myoblasts (Wu, Tsai, Wang, Wu, Wang & Lee, 1996) it is possible that this phenomenon exists in many other cells. This intracellular acidosis may influence the ability of glial cells to regulate the pHï of the microenviroment and may probably contribute, in part, to the neuronal activity and cytotoxic cell oedema seen during brain ischaemic reperfusion.…”
Section: Lactate Productionsupporting
confidence: 55%
“…These compartments store high mM levels of calcium, and a functional exchange of Ca 2 þ for H þ occurs at both endosomes 31 and lysosomes. 32 Due to its induction of fast ATP hydrolysis, hydrogen peroxide rapidly decreases cytosolic pH, 25 thus setting the right conditions for accelerated proton/calcium exchange at these organelles. However, abrogation of peroxide-induced cytosolic acidification in HeLa cells using a pH clamp did not significantly affect the calcium rise, showing that proton/ calcium exchange is not an important mechanism of oxidative calcium release.…”
Section: Discussionmentioning
confidence: 99%
“…Lysosomal calcium, which has been recently measured at about 500 mM, is much less sensitive to extracellular calcium depletion. 32 Similar to endosomal calcium, lysosomal calcium varies reciprocally with organelle proton concentration; so the large cytosolic acidification resulting from peroxide exposure 25 may in principle release the divalent in exchange for protons. An important source of protons in this case is the hydrolysis of ATP due to glycolytic inhibition by peroxide.…”
Section: Acidic Compartmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been used in several studies to investigate different cellular mechanisms in cardiomyocytes (Sipido & Marban 1991, Wu et al 1996, Chen et al 2000 and has been shown to be responsive to IGF-I (Chen et al 1995, Bahr et al 1997.…”
Section: Introductionmentioning
confidence: 99%